Phytoplankton Biodiversity of Danau Panjang, Lubuk Siam Village, Siak Hulu District, Kampar District, Riau - Rachmatunnisa, Rachmatunnisa; Fauzi, Muhammad; Fajri, Nur El (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Danau Panjang is a natural lake located in Lubuk Siam Village. The variety of activities in Danau Panjang can affect phytoplankton biodiversity. Phytoplankton is an important factor for the life of fish and all kinds of biota that live in water as primary producers. The presence of phytoplankton will determine the quality and condition of a body of water. Danau Panjang, as one of the oxbow lakes, currently rarely has any additional discharge from the main river, so it is feared that phytoplankton diversity will be low. This study aims to determine the type and abundance of phytoplankton and phytoplankton biodiversity and the results of the analysis of environmental factors on phytoplankton biodiversity in Danau Panjang. Phytoplankton biodiversity and water quality parameters consisting of temperature, brightness, depth, pH, CO2, DO, nitrate, and phosphate were observed in September-October 2023. Phytoplankton samples and water quality measurements were taken at three sampling points, three times with an interval of two weeks. Phytoplankton abundance ranged from 2383-7098 cells/L, and 10 phytoplankton classes were found. Phytoplankton biodiversity in Danau Panjang illustrates a relatively stable condition. The species richness index in Weeks 1, 2, and 3 ranged from 3.51-5.52 in the good category. The diversity index in Weeks 1, 2, and 3 ranged from 2.06-3.82, with a high level of diversity. The dominance index in Weeks 1, 2, and 3 ranged from 0.12-0.38, indicating that there was no dominant species. The uniformity index in Weeks 1, 2, and 3 ranged from 0.39-0.69, where uniformity was in balance. In general, the water quality in Weeks 1, 2, and 3 is not much different and is favorable for phytoplankton growth when viewed from the quality standards of class III of PP No. 22 of 2021.